1980
DOI: 10.1152/jappl.1980.48.5.826
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urinary bladder afferents on respiration

Abstract: The electrical activity of phrenic and recurrent laryngeal motoneurons was recorded during activation of urinary bladder afferents in pentobarbital-anesthetized, paralyzed, artificially ventilated cats. Distension or spontaneous neurogenic contraction of the bladder decreased the amplitude and frequency (bursts/min) of the burst activity in these two nerves. The decrease in frequency was due mainly to a prolongation of the interburst interval (duration of expiration). Similar effects were observed during low-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 4 publications
2
7
1
Order By: Relevance
“…Second, correlation and multiple regression analyses showed that MIP and pyramidal tract involvement did not emerge as predictors of the responsiveness to hypercapnia and hypoxia; this excludes spinal cord disease as a causative factor for the disturbed breathing control in our MS patients. Last, the fact that the pneumotaxic and micturition cen-ters are anatomically and functionally so closely related 20,22 supports our finding that MS patients with DSD are more prone to disturbances in ventilatory control. DSD can, however, also be caused by spinal lesions of the pyramidal tract, but no correlation was found between the degree of pyramidal tract lesions and the degree of sphincter dysfunction in our patients.…”
Section: Discussionsupporting
confidence: 78%
“…Second, correlation and multiple regression analyses showed that MIP and pyramidal tract involvement did not emerge as predictors of the responsiveness to hypercapnia and hypoxia; this excludes spinal cord disease as a causative factor for the disturbed breathing control in our MS patients. Last, the fact that the pneumotaxic and micturition cen-ters are anatomically and functionally so closely related 20,22 supports our finding that MS patients with DSD are more prone to disturbances in ventilatory control. DSD can, however, also be caused by spinal lesions of the pyramidal tract, but no correlation was found between the degree of pyramidal tract lesions and the degree of sphincter dysfunction in our patients.…”
Section: Discussionsupporting
confidence: 78%
“…7,9,10 We did not observe any consistent responses in respiration. The discrepancy is probably due to the differences in species and experimental conditions.…”
Section: Discussioncontrasting
confidence: 55%
“…In the absence of block of the afferent pathway, inadequate anesthesia may produce an unstable cardiovascular status when stimuli are applied 2,6 In addition to the cardiovascular reflexes, both spontaneous contraction and passive distension of the bladder may produce inhibition of respiratory motor neurone activity in anesthetized or decerebrate cats. [7][8][9][10] These findings may indicate that changes in bladder volume could produce abnormal breathing during light general anesthesia.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In considering our findings, we should remember that non-vagal afferent influences act on the pattern of breathing. Electrical stimulation of the splanchnic nerve in rabbits (Siegelova, 1976) and cats (Albano and Garnier, 1983) and the more physiological stimulus of urinary bladder distention (Schondorf and Polosa, 1980) inhibited phrenic activity. There is little doubt, however, that vagal afferents are a major determinant of the pattern of breathing in the type of preparation used in the present series of experiments.…”
Section: Discussionmentioning
confidence: 99%